Who Makes the Decisions? Women’s Participation in Canadian Unions - Boehm, Marina C. (Industrial Relations Centre, Queen's University, 1991)
The purpose of this report is to determine whether women are increasingly being involved in the decision-making process of Canadian unions. The scope of review of this report is restricted to public sector unions and one private sector union in the province of Ontario. A combination of methods were utilized in completing this study, including an overview of existing research, a review of statistical data, and an analysis of policy statements, convention resolutions and general union literature. The results of this review indicate that labour organizations have paid significant and increasing attention to women’s issues over the past 15 to 20 years; union policies have encompassed aspects of women’s inequality within the union, in the workplace and in society. Many unions, particularly the central labour organizations, have adopted policies of internal affirmative action, they have increased the amount of education available to staff and union members on women’s issues, they have implemented policies providing child care services during union functions such as conventions and workshops, and they have provided regular coverage of women’s issues in membership publications. While these progressive policies are a positive indication of the unions’ commitment to attaining women’s equality, they are not a guarantee of prolonged or significant increases in women’s participation in union decision-making activities. Labour organizations must be careful not to overestimate the effectiveness of their policies, and they must redouble their efforts to win the battle against discrimination within their hierarchies and structures. To this end, unions must ensure that their policies are fully implemented in practice. They must also continue to educate their staff and union members about the benefits of providing women with equal opportunities. The labour movement can only grow stronger through greater solidarity between its union sisters and brothers.